Impacto da geração distribuída na reconfiguração em sistemas de distribuição de energia elétrica - Leite, Matheus Diniz Gonçalves (2022)
Energy consumption has grown substantially. In the last 30 years, the world demand for electric energy has more than doubled, with an increase of 50% in this value expected until the year 2050. In this context of increased demand and expansion of the energy matrix, the Distributed Generation (DG), characterized as the generation of energy close to the end user, has been spreading in the Electric Power Distribution System (EPDS). Between 2019 and 2021, new DG units connected to the Brazilian system provided an extra generation more than eight times greater than the power generated by DG in the years between 2009 and 2018. The allocation of DG units, when carried out efficiently, allows the reduction of active losses in the conductors, improvement of the voltage profile on the buses, continuity of local supply in case of contingencies in the system and relief at peak load times. In this work, an analysis of the impact of DG on total active losses in conductors and on the effectiveness of the EPDS reconfiguration is made. Different scenarios for the location of the DG units and different levels of demand supplied by them are analyzed. The reconfiguration is performed through a meta-heuristic that is based on the Prim methodology and on the Branch Exchange heuristic to coordinate the search processes through the search space. The proposed algorithm is applied to four test systems of different sizes and characteristics – 14, 33, 84 and 415 buses. The results corroborate that the allocation of DG units in buses far from the substation presented, for most cases, the best cost-benefit relationship between the number of units to be allocated and the reduction of total active losses. The insertion of DG in the system impacted the effectiveness of the reconfiguration, which proved to be more efficient for high levels of active power injection in the buses.